Entrepreneurship Game Apps to Enhancement Student Skill Thinking Analytic in Class Online - Pratikto, Heri; Hanafiya, Rizal; Ashar, Muhammad; Akbar, Muhammad Iqbal; Harsono, Yudi Tri (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The use of educational entrepreneurship game apps as a medium for an online class for students to improve analytical skills regarding business processes. Learning that is only through gamification in game learning. This learning is carried out on a number of students who have the ability to play games well. There is also a desire to study business without using entrepreneurship textbooks as the object of this study. Game-based mobile apps development using entrepreneurial learning materials such as laundry and beverage sales is designed using the Design Thinking Process method. With a game prototype made according to the real market location and market potential which is quite profitable. Determination of initial capital is very important in this educational game to successfully play the game until the final level. (there are 5 trial levels). The results obtained from this gameplay show an increase in entrepreneurial analysis in students with the ability to answer post-test questions well with an average of 88.2 percent with an average game time of 42.8 minutes per level